PENGGUNAAN MIXED METHOD USABILITY TESTING (EYE TRACKING METHOD DAN COGNITIVE WALKTHROUGH (STUDI KASUS: WEBSITE JURUSAN SISTEM INFORMASI FAKULTAS ILMU KOMPUTER UNIVERSITAS SRIWIJAYA): Case Study: Website of The Department of Information Systems, Faculty of Computer Science, Sriwijaya University - Putra, Pacu; Oktadini, Nabila Rizky; Hardiyanti, Dinna Yunika; Larasati, Salsabila; Putri, Nyayu Dwi Tarisa (The Indonesian Journal of Computer Science, 2025)
Universitas Sriwijaya is one of the state universities in Indonesia. Universitas Sriwijaya has 10 faculties, one of which is the Faculty of Computer Science. Information Systems is one of the departments in the Faculty of Computer Science, Sriwijaya University. Based on the observation results, the Department of Information Systems has just updated the appearance of its website. To determine the level of usability of the website, this research uses two methods, namely eye-tracking method and cognitive walkthrough. The activities that are the research material in this research include searching for lecturers' schedules, downloading final project guidelines and searching for course codes. As a result of the cognitive walkthrough method, the activity of searching for lecturers' timetables has the lowest success rate of 0%, followed by the activity of searching for course codes with 40% and the activity of downloading final project guidelines with 80%. In addition, the research continued using the eye-tracking method to identify areas of confusion for the respondents and to understand the emotional level of the respondents when carrying out these activities. It can be seen that the average respondent is still confused or unfocused when working on the pre-defined activities.